Intelligent Transformation and Corporate Financialization - Ma, Shenyu (Transactions on Economics, Business and Management Research, 2024)
Based on the data of manufacturing enterprises listed in the Shanghai and Shenzhen A-shares from 2007 to 2021, this paper empirically examines the impact of intelligent transformation on corporate financialization, its mechanisms, and the moderating effects on their relationship. The study finds that intelligent transformation has a significant negative impact on corporate financialization, namely, intelligent transformation inhibits the degree of corporate financialization. The results of the moderating effect regression show that the inhibitory effect of intelligent transformation on financialization activities is more pronounced in state-owned enterprises and firms with greater financing constraints; a highly competitive market negatively moderates the inhibitory effect of intelligent transformation on corporate financialization activities. Mechanism tests prove that intelligent transformation can inhibit corporate financialization by increasing the return on investment in the real sector and curbing the scale of shadow banking activities of enterprises, thereby changing the flow of capital between the real and financial sectors. This paper supplements the economic consequences of intelligent transformation from the perspective of corporate financialization and provides empirical evidence for government policies on intelligent transformation and corporate strategies for intelligent innovation.